Whole-body vibration and occupational physical performance: a review - Savage, R.; Billing, D.; Furnell, A.; Netto, Kevin; Aisbett, B. (Springer Verlag, 2015)
© 2015 Springer-Verlag Berlin Heidelberg Introduction: In the occupational environment, there are a considerable number of stressors that can affect physical performance in job tasks. Whole-body vibration (WBV), which arises from vehicle transit, is one such stressor that has been demonstrated to alter human function in several ways. This study identifies the known physical changes to human function which result from WBV, to comment on changes which may translate to performance in physically demanding occupational tasks. Methods: A systematic review is performed on the literature relating to changes in the neuromuscular, physiological and biomechanical properties of the human body, when exposed to WBV. Selection criteria are constructed to synthesise articles which strictly relate to in-vehicle WBV and physical responses. Results: In total, 29 articles were identified which satisfied the criteria for inclusion. A range of physical responses produced from WBV are presented; however, little consistency exists in study design and the responses reported. Discussion: Given the inconsistency in the reported responses, the precise changes to human function remain unknown. However, there is sufficient evidence to warrant the design of studies which investigate occupationally relevant physical performance changes following WBV.